Bibliography of Professor Jerzy Topolski’s works for the years 1998-2001 - Łabędzka-Topolska, Maria (Studia Historiae Oeconomicae, 2001)
Continuation of the bibliography of Prof. J. Topolski's works published in volume 23 of SHO.